2009
DOI: 10.4103/0971-4065.53323
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of clopidogrel to prevent primary arteriovenous fistula failure in hemodialysis patients

Abstract: The optimal vascular access for chronic maintenance hemodialysis is the arteriovenous fistula (AVF). Several studies suggest a role for antiplatelet agents in the prevention of primary AVF failure. A double-blind, randomized trial was conducted to assess the efficacy and safety of clopidogrel in hemodialysis patients. Ninety three patients were randomized to receive 75 mg/daily of clopidogrel or placebo. The treatment was initiated 7–10 days prior to scheduled access surgery and continued up to six weeks posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…23 During surgery, traction of the arteries can lead to postoperative vasospasm, decreased blood flow, and endovascular damage. 24,25 These factors contribute to formation of thrombus after fistula formation, which results in failure of internal fistula function. 14 A recent study reported by Kim et al.…”
Section: Discussionmentioning
confidence: 99%
“…23 During surgery, traction of the arteries can lead to postoperative vasospasm, decreased blood flow, and endovascular damage. 24,25 These factors contribute to formation of thrombus after fistula formation, which results in failure of internal fistula function. 14 A recent study reported by Kim et al.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few small trials evaluating pharmacological agents aimed at reducing the early thrombosis rate. [ 8 13 14 15 ]. These trials utilized the antiplatelet agents, aspirin, sulphinpyrazone, and clopidogrel and varied in size from as few as 5 patients up to 250 patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 10 17 ] In view of these postulated mechanisms of AVF failure, possible clinical benefit of antiplatelet therapy has been proposed for prevention of AVF failure. [ 13 14 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…A native fistula is the ideal type of access as the risk of complications and need for interventions are at lowest, and it also provides a longterm patency. 6 Nevertheless, a major obstacle in the long-term success of hemodialysis therapy is AVF dysfunction. 5 In AVF creation, the best method to decrease the risk of primary AVF failure involves introducing hemodialysis vascular access early, performing vascular mapping, and assessing newly created AVFs at four weeks.…”
Section: Introductionmentioning
confidence: 99%